Electronic occurrence bulletin in the state of São Paulo: Artificial intelligence as an innovation proposal - Dos Santos, José Eduardo Lourenço; Neto, Mário Furlaneto [UNESP]; Pereira, Fábio Dacêncio (My University, 2020)
Objective: Within the scope of e-Gov and the digital design process (digital by design), it is intended to undestand the Electronic Police Report (EPR) system of the Civil Police of the State of São Paulo aiming to contribute the optimization of the system and results. Methodology: Case analysis and methodological procedures for doctrinal and legislative review. Results: It is proposed a conceptual model of intelligent assistant based on conversational artificial intelligence (AI) and natural language processing, aggregating the organization, classification and preparation of data, machine learning algorithms, affective computing and situational awareness. The intelligent assistant will interact with the citizen through a chatbot and, added to the natural language processing, it will be able to contribute to improve the policeman's situational awareness. In addition, the use of artificial intelligence upon the support of affective computing and situational awareness may allow triggering of alerts in emergency situations. Contributions: the conceptual model of intelligent assistant proposed is capable of innovating and enhancing the results of the EPR, as well as improving transparency, speed and efficiency in decision making by the police delegate aiming to foster the level of assertiveness, productivity and completeness of the electronic services offered by the Electronic Police Station of the Civil Police of the State of São Paulo.
Boletim de ocorrência eletrônico no estado de São Paulo: Inteligência artificial como proposta de inovação
Keywords: Artificial intelligence; Electronic document; Electronic government; Public security; Tecnologic innovation